Case report: Minimally invasive excision of multifocal cardiac papillary fibroelastomas involving right atrium and aortic valve - Teng, Peng; Hu, Peng; Yuan, Shuai; Ma, Liang (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac papillary fibroelastomas (CPFs) are rare benign cardiac tumors most commonly found on left-sided cardiac valves. Right atrial CPFs are extremely rare, accounting for only 2% of all CPFs. Median sternotomy is a typical approach for surgical excision of CPFs in most cases. Herein, we report an extremely rare case of multifocal CPFs involving the right atrium and aortic valve that were surgically excised via minimally invasive right anterolateral thoracotomy. Case Summary A 59-year-old Chinese man was admitted because of an incidental finding of a right atrial mass on transthoracic echocardiography during a routine check-up. The mass was initially diagnosed as a myxoma, and the patient was scheduled for minimally invasive excision via right anterolateral thoracotomy. An additional mass on the non-coronary cusp of the aortic valve was identified using intraoperative transesophageal echocardiography. The patient still underwent complete tumor excision via right anterolateral thoracotomy. Both neoplasms were pathologically diagnosed as CPFs. Conclusions This case highlights the need for a comprehensive cardiac evaluation of cardiac tumors because CPFs can manifest as multifocal lesions. Moreover, minimally invasive surgery is highly feasible as the CPF can be easily excised, and the valve can usually be preserved.